2022
DOI: 10.3390/ijerph19031161
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Participation in Rural Areas: A Case Study

Abstract: Sport participation and physical activity promotion have been intensively studied, especially regarding large cities. However, in many cases, rural municipalities have comparatively reduced services, including health care, due to the low profitability that these have for companies and entities. In this sense, the purpose of this article was to describe a case study of the promotion of physical activity in rural areas based on the results of a European project. Carried out in a rural municipality of around 8500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
0
0
2
Order By: Relevance
“…European and national sports participation surveys have shown that the practice of outdoor activities in non-competitive, informal groups with aims to improve or maintain health is growing in all EU countries. Public spaces such as streets, parks, and mountains are favored locations to play sports in most countries [71]. We found statistically significant differences related to participation in sports activities by the degree of mobility, but no association between participation in this kind of activities and the need for assistive devices, buildings' accessibility, or public places' accessibility.…”
Section: Participation In Sports Activitiesmentioning
confidence: 60%
“…European and national sports participation surveys have shown that the practice of outdoor activities in non-competitive, informal groups with aims to improve or maintain health is growing in all EU countries. Public spaces such as streets, parks, and mountains are favored locations to play sports in most countries [71]. We found statistically significant differences related to participation in sports activities by the degree of mobility, but no association between participation in this kind of activities and the need for assistive devices, buildings' accessibility, or public places' accessibility.…”
Section: Participation In Sports Activitiesmentioning
confidence: 60%
“…This may be due to the more open environment and easier accessibility to open spaces in rural areas. However, it was also identified that children in urban areas may face access barriers to organized sports and physical activity facilities, such as parks, sports fields or sports clubs (Marcen et al, 2022). Therefore, improving accessibility and opportunities to participate in physical activity in urban areas is important to ensure that the benefits of sport are equally enjoyed by all children, regardless of their social or geographical status.…”
Section: Discussionmentioning
confidence: 99%
“…Subjacente a esse processo de reconfiguração do esporte e da Educação Física à luz das dinâmicas de conhecimento na sociedade de risco, está, como já dito, uma revisão da hierarquia das atividades motrizes. O trekking e demais tipos de caminhada outdoor, por exemplo, já se elencam como algumas das práticas motrizes mais realizadas no mundo (Puig, 2016;Grima et al, 2017;Marcen et al, 2022;Lee et al, 2022), estando, em alguns casos, inclusive, a frente de práticas esportivas mais tradicionais, o que endossa, em alguma medida, o abalo que a tradição sofreu nos últimos anos nos mais diferentes domínios da ação humana (Souza, 2021). No Brasil, de acordo com alguns levantamentos, a caminhada outdoor já figura entre as atividades físicas mais predominantes (IBGE, 2017; Lima et al, 2019).…”
Section: Um Novo Contrato Motor Na Mod-ernidade Tardia? Autobiografia...unclassified
“…No Brasil, de acordo com alguns levantamentos, a caminhada outdoor já figura entre as atividades físicas mais predominantes (IBGE, 2017; Lima et al, 2019). Além disso, a própria literatura internacional já vem demonstrando uma maior participação dos agentes sociais em esportes individuais, o que também ratifica o cenário de individualização em que vivemos (Hallmann e Petry, 2013;Llopis-Goig, 2016;Scheerder et al, 2017;Lee et al, 2022;Marcen et al, 2022). Porém, cabe destacar que a dinâmica do self nada tem a ver com um comportamento egocêntrico ou atomístico (Souza, 2021).…”
Section: Um Novo Contrato Motor Na Mod-ernidade Tardia? Autobiografia...unclassified